Perancangan UI/UX Sistem Kearsipan Dinas Komunikasi Dan Informatika Kabupaten Oku Menggunakan Framework Codeigniter 3 - Felli Afriyanti; Nurul Huda; Syahril Rizal; Rahayu Amalia (STMIK Banjarbaru, 2025)
Digital transformation in archive management has become a critical need for government institutions, including the Department of Communication and Informatics (Diskominfo) of Ogan Komering Ulu (OKU) Regency. This study aims to design a web-based archiving system focusing on user interface (UI) and user experience (UX) aspects using the CodeIgniter 3 framework. The methodology applied is Design Thinking, which involves the stages of empathize, define, ideate, prototype, test, and implement. The system is designed to simplify the recording, storage, retrieval, and management of incoming and outgoing letters in a digital format. The results show that the system significantly improves efficiency, accuracy, and security in archive management. Testing using the black-box method confirms that all functionalities work as expected. This system provides a solution to the limitations of manual archiving, which is slow, vulnerable to damage, and difficult to track, and supports enhanced public service quality within Diskominfo OKU.Keywords: UI/UX; Digital archiving; CodeIgniter 3; Design Thinking; Diskominfo OKU AbstrakTransformasi digital dalam pengelolaan arsip menjadi kebutuhan penting bagi instansi pemerintah, termasuk Dinas Komunikasi dan Informatika (Diskominfo) Kabupaten Ogan Komering Ulu (OKU). Penelitian ini bertujuan untuk merancang system kearsipan berbasis web yang focus pada aspek antarmuka pengguna (UI) dan pengalaman pengguna (UX). Menggunakan framework CodeIgniter 3. Metode yang digunakan adalah Design Thinking, melalui tahapan empathize, define, ideate, prototype, test, dan implement. System dirancang untuk mempermudah pencatatan penyimpanan, pencarian, dan pengelolaan surat masuk dan surat keluar secara digital. Hasil penelitian menunjukkan bahwa system ini mampu meningkatkan efisiensi, akurasi, serta keamanan dalam pengelolaan arsip. Pengujian menggunakan blackbox testing menunjukkan seluruh fungsi berjalan sesuai harapan. System ini memberikan solusi terhadap kendala arsip manual yang lambat, rentan rusak, dan sulit ditelusuri, serta mampu meningkatkan kualitas layanan public di lingkungan Diskominfo OKU.Kata kunci: UI/UX; Kearsipan digital; CodeIgniter 3; Design Thinking; Diskominfo OKU